Hypertension and Diabetes Mellitus Screening as an Effort to Prevent Degenerative Diseases in Matahari Pan Factory Workers in Cikoneng District, Ciamis Regency - Aliza Puziawati; Ninda Aulia Fitriani; Risma Amelia; Zilfa Auliyaa Faidah; Zahra Bilqis Syahidah; Fajar Permana (Jurnal Pengabdian Bidang Kesehatan, 2025)
Degenerative diseases such as hypertension and diabetes mellitus are increasingly prevalent among both productive-age and elderly populations, including industrial workers. This community service activity aimed to conduct early detection and provide health education related to hypertension and diabetes among workers at Pabrik Wajan Matahari, Cikoneng Subdistrict, Ciamis Regency. The methods included physical examinations (blood pressure and blood glucose) and personalized counseling based on the examination results. The activity involved 30 active worker participants. Results revealed that 66.7% had a history of hypertension and 96.7% had a history of diabetes mellitus. These findings indicate a high prevalence of degenerative diseases among workers and underscore the importance of continuous promotive-preventive interventions in the workplace. Follow-up efforts should include routine screenings, healthy lifestyle education, and cross-sector collaboration to reduce the risk of non-communicable diseases among industrial workers.